2007
DOI: 10.1177/0890334407307882
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Attitudes and Reported Problems in a National Sample of WIC Participants

Abstract: Recent reports indicate that breastfeeding rates continue to be dramatically lower among WIC participants, compared with other US mothers. The WIC Infant Feeding Practices Study was a nationally representative 1-year longitudinal study of WIC participants that obtained information about attitudes regarding infant feeding and about infant-feeding practices. Hispanic mothers were most likely to agree with statements about benefits of breastfeeding, and Black mothers were most likely to agree with statements abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 50 publications
1
91
2
3
Order By: Relevance
“…In one study, women who had Medicaid insurance and were enrolled in WIC programs were less likely to breastfeed (Chin et al, 2008). In another study, more than 50% of women enrolled in WIC initiated breastfeeding, yet only 25% of those women continued breastfeeding at 6 months (McCann et al, 2007). Hospitals where the Baby-Friendly Hospital Initiative was implemented had increased breastfeeding rates regardless of the socioeconomic status of women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study, women who had Medicaid insurance and were enrolled in WIC programs were less likely to breastfeed (Chin et al, 2008). In another study, more than 50% of women enrolled in WIC initiated breastfeeding, yet only 25% of those women continued breastfeeding at 6 months (McCann et al, 2007). Hospitals where the Baby-Friendly Hospital Initiative was implemented had increased breastfeeding rates regardless of the socioeconomic status of women.…”
Section: Discussionmentioning
confidence: 99%
“…Fears of inadequate milk supply, painful breasts, and latching difficulties can be addressed through patient education (Hannula et al, 2008;Swanson & Power, 2005). Women who participated in a study by McCann et al (2007) reported concerns about clinicians have adequate knowledge and skills for educating and supporting women to increase the duration of breastfeeding (Taveras et al, 2003).…”
Section: Reasons For Breastfeeding Cessationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we were not able validate self-report against clinical assessment. Perception of insufficient milk supply is common, 44 and such perception is correlated with low parenting self-efficacy. 45 Of note, a recent study found that parenting magazines targeting lowincome women were more likely to focus on difficulties with breastfeeding than was a magazine targeting high-income women.…”
Section: Prevalence Of Disrupted Lactation 409mentioning
confidence: 99%